2010
DOI: 10.1097/ccm.0b013e3181d8cc1d
|View full text |Cite
|
Sign up to set email alerts
|

Long-term mortality and quality of life in sepsis: A systematic review*

Abstract: Patients with sepsis have ongoing mortality beyond short-term end points, and survivors consistently demonstrate impaired quality of life. The use of 28-day mortality as an end point for clinical studies may lead to inaccurate inferences. Both observational and interventional future studies should include longer-term end points to better-understand the natural history of sepsis and the effect of interventions on patient morbidities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

23
397
3
28

Year Published

2010
2010
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 529 publications
(467 citation statements)
references
References 57 publications
23
397
3
28
Order By: Relevance
“…In addition to the existing interest in therapeutic approaches for sepsis (where therapy remains supportive and no specific treatments have been identified, even after decades of intensive research), there is also an increasing interest in approaches to improve the health of sepsis survivors (27,32). Molecular Medicine…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the existing interest in therapeutic approaches for sepsis (where therapy remains supportive and no specific treatments have been identified, even after decades of intensive research), there is also an increasing interest in approaches to improve the health of sepsis survivors (27,32). Molecular Medicine…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have investigated long-term sequelae of CAP [16,[19][20][21][22]. JOHNSTONE et al [16] recently investigated longterm morbidity and mortality of patients with CAP requiring hospitalisation using multiple linked administrative databases in Canada after a median follow-up of 3.8 yrs.…”
Section: Multivariable Analysismentioning
confidence: 99%
“…However, less extensive research has been conducted for a better understanding of factors influencing longterm mortality after initial hospitalisation of CAP patients. Previous data suggest that patients who survive an initial CAP episode are at increased risk of mortality and recurrent infections in the months following hospital discharge [16][17][18][19][20][21][22], especially in patients .40 yrs of age [23]. CAP may be a consequence of a patient's poor general condition and severe underlying comorbidities, which place patients at risk of further infections and mortality [18].…”
mentioning
confidence: 99%
“…For example, survivors of acute respiratory distress syndrome (ARDS) have prolonged 6-minute walk times, executive dysfunction, other neuropsychiatric deficits, and diminished ability to return to work (2-13). Numerous studies have found quality of life among survivors of critical illness (14, 15), severe sepsis (16,17), and ARDS (4-8, 13, 18) to be abnormally low.Patients surviving critical illness have limitations and disabilities somewhat characteristic of an older adult population. Rubenfeld recently postulated a "progeric hypothesis" that the sequelae of critical illness mirror accelerated aging (19).…”
mentioning
confidence: 99%
“…For example, survivors of acute respiratory distress syndrome (ARDS) have prolonged 6-minute walk times, executive dysfunction, other neuropsychiatric deficits, and diminished ability to return to work (2-13). Numerous studies have found quality of life among survivors of critical illness (14, 15), severe sepsis (16,17), and ARDS (4-8, 13, 18) to be abnormally low.…”
mentioning
confidence: 99%